Treatment of Stress Urinary Incontinence with Duloxetine Hydrochloride - Sweeney, Danielle D. (MedReviews, LLC, 2005)
Currently, there are no approved medications for the treatment of stress urinary incontinence (SUI) in the United States. The effectiveness of duloxetine in the treatment of SUI is linked to its inhibition of presynaptic neuronal reuptake of serotonin and norepinephrine in the central nervous system, resulting in elevated levels of serotonin and norepinephrine in the synaptic cleft. In animal studies, this agent leads to an increase in nerve stimulation to the urethral striated sphincter muscle. A similar mechanism in women is believed to result in stronger urethral contractions, with improved sphincter tone during urine storage and physical stress. In 3 randomized, placebo-controlled clinical trials, patients receiving duloxetine had a statistically significant and clinically relevant reduction in the number of incontinence episodes and a corresponding improvement in quality of life. If this use of duloxetine is approved by the U.S. Food and Drug Administration, as it has been by the European regulatory agencies, it will be the first drug indicated for the treatment of SUI. This pharmacologic therapy is an additional option for women and is likely to become an integral component of patient management.